Sleep Respiratory Disorders and Clinical Profile in Patients with Type 2 Diabetes Mellitus - Fontela, Paula Caitano; Winkelmann, Eliane Roseli; Pretto, Luciana Meggiolaro; Berlezi, Evelise Moraes (International Archives of Otorhinolaryngology, 2015)
Introduction Sleep respiratory disorders (SRDs) are often found in patients with type 2 diabetes mellitus (T2DM).Objective The aim was to establish the prevalence of risk to develop an SRD using the Clinical Berlin Questionnaire (CBQ) and Epworth Sleepiness Scale (ESS) in patients with T2DM and verifying the correlation of anthropometric measurements and life quality (LQ) with ESS.Methods A descriptive and analytical study of a case series evaluating 208 patients with T2DM, submitted to clinical and biochemical evaluation and implementation of CBQ, ESS, and WHOQOL-bref to evaluate LQ.Results Mean age was 60.8 ± 8.8 years, and 65.4% were women. Most diabetics were overweight (36.1%), and 29.8% were class I obese. One-third had positive risk signals for a SRD, with 87.0 and 34.1% having high risk in CBQ and sleep disorders in ESS, respectively. There was a significant difference in the general LQ between the low- and high-risk groups in the CBQ.Conclusion In this scenario, it is noteworthy that the active search for sleep disorders must start from simple methods, such as application of protocols.
Keywords: health evaluation; epidemiology; public health; sleep disorders for excessive somnolence